Star-crossed egg tarts - Chow, Jennifer J. (Chow, Jennifer J. Magical fortune cookie novel, 2025)
"Jin Bakery has been asked to cater the Lum-Wu outdoor wedding at Pixie Park. The day of the ceremony, Felicity is finishing the 'cake' of tiered egg tarts as the wedding party arrives for the ceremony. When one of the groomsmen, Miles Wu, doesn't arrive, Felicity's best friend and local florist Kelvin generously steps in for him and the wedding goes smoothly--until cake cutting time. That's when Felicity finds Miles' dead body beneath the table with her egg tarts display, stabbed by Kelvin's gardening shears. With the detective's sights on Kelvin, Felicity starts sleuthing away to prove his innocence."--